RELAÇÃO DOS INSÉTOS ENCONTRADOS SOBRE PLANTAS DO ESTADO DE S.PAULO NOS ANOS DE 1936-1937 - Mendes, Luiz O. T. (REVISTA DE AGRICULTURA, 2015)
RELAÇÃO DOS INSÉTOS ENCONTRADOS SOBRE PLANTAS DO ESTADO DE S.PAULO NOS ANOS DE 1936-1937